Pacing mobilities : timing, intensity, tempo and duration of human movements - Amit, Vered, 1955-; Salazar, Noel B., 1973- (Worlds in motion (Berghahn Books), 2020)
"Turning the attention to the temporal as well as the more familiar spatial dimensions of mobility, this volume focuses on the momentum for and temporal composition of mobility, the rate at which people enact or deploy their movements as well as the conditions under which these moves are being marshalled, represented and contested. This is an anthropological exploration of temporality as a form of action, a process of actively modulating or responding to how people are moving rather than the more usual focus in mobility studies on where they are heading"--